2014
DOI: 10.1039/c3em00537b
|View full text |Cite
|
Sign up to set email alerts
|

Photoreactivity of the fungicide chlorothalonil in aqueous medium

Abstract: The photoreactivity of chlorothalonil was studied by means of steady-state irradiation and laser-flash photolysis. Experiments were conducted in water containing acetonitrile as a co-solvent. This fungicide undergoes very slow phototransformation in the first stages of the reaction, but the consumption profile is auto-accelerated. To understand the reaction mechanism, we undertook a detailed study of the rates, products and transient species. The rates and photoproduct distribution vary greatly with the oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 19 publications
(43 reference statements)
1
14
0
Order By: Relevance
“…This is in line with the involvement of 3 CT* in the reaction. 32,33 Solution deoxygenation also drastically increases the rate of CT phototransformation in the presence of HSs. The ratio (r CT ) HS argon /(r CT ) HS aerated , where (r CT ) HS argon is the rate of CT phototransformation in the presence of HS and in the absence of oxygen, is between 52 and 88 (Table 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in line with the involvement of 3 CT* in the reaction. 32,33 Solution deoxygenation also drastically increases the rate of CT phototransformation in the presence of HSs. The ratio (r CT ) HS argon /(r CT ) HS aerated , where (r CT ) HS argon is the rate of CT phototransformation in the presence of HS and in the absence of oxygen, is between 52 and 88 (Table 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It shows the same m/z value in HPLC/MS but with a shorter HPLC retention time than 4-hydroxychorothalonil and is identified to 2hydroxychorothalonil. 33 In polychromatic light, HSs reduces the rate of formation of this compound. At 406 nm, this compound is only detected in the irradiated solutions containing HSs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…142) The LFP study with quenching by 3 O 2 showed T* as a key intermediate in the photolysis of chlorothalonil, and reductive dechlorination was the main reaction in water. 27,28) Photosubstitution seems more favorable in the aqueous photolysis of pesticides that have a chlorinated aryloxy moiety. Phenoxyacetic herbicides, such as 2,4-D, 143) 2,4,5-T, 113) and triclopyr, 144) generally produced the corresponding 2-OH derivatives; however, reductive dechlorination at the 4-position was more favorable for dichlorprop.…”
Section: Dehalogenation 3151 Dechlorinationmentioning
confidence: 99%
“…68) Not only electronic transitions with E S and E T values relevant to direct photolysis 50,[69][70][71] but also threedimensional structures in excited states and of reactive intermediates 41,[70][71][72] can be examined using TD-DFT calculations. Since the calculations generally suppose an isolated molecule in a vacuum, a solvation effect has been taken into account in some cases, indirectly by using a polarized continuum 28,33,50) or Onsager's cavity model, 70,73) or directly by introducing water molecules into the calculations. 49) A bond liable to be photocleaved 53,73,74) together with the preference of a homolytic or heterolytic mechanism 33,75) can be conveniently evaluated by its dissociation energy.…”
Section: Theoretical Approachmentioning
confidence: 99%